DEVELOPING INTERCULTURAL COMPETENCE THROUGH ENGLISH LANGUAGE INSTRUCTION IN HIGHER EDUCATION - Tadjibaeva Adila Ergashevna (Modern American Journals, 2025)
In an increasingly globalized world, the development of intercultural competence has become a critical component of higher education. English language instruction, especially in non-native contexts, plays a pivotal role in fostering students’ ability to communicate effectively across cultures. This paper explores the theoretical foundations, pedagogical strategies, and practical implementations of intercultural competence within English language teaching (ELT) in higher education institutions. It critically examines how curriculum design, classroom discourse, and culturally responsive teaching methods contribute to students’ awareness, attitudes, knowledge, and skills related to intercultural communication. Drawing on case studies from diverse academic settings, the research highlights the challenges and best practices for integrating intercultural learning outcomes into English language programs. The findings underscore the importance of teacher training, institutional support, and learner-centered approaches to promote inclusive, reflective, and globally competent graduates. This study concludes with strategic recommendations for enhancing intercultural education through English language instruction, aligning with internationalization goals and UNESCO's global citizenship education framework.
Keywords: Intercultural competence, English language teaching, higher education, global communication, language pedagogy, cultural awareness, internationalization, curriculum integration.